Pola Konsumsi dan Kebiasaan Konsumsi Tablet Tambah Darah (TTD) dengan Kejadian Anemia pada Remaja Putri di SMKN 1 Manggis, Kabupaten Karangasem - Melina Permana Sari; Pande Putu Sri Sugiani; Gusti Ayu Dewi Kusumayanti (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2018)
One of the nutritional problems in adolescents and adults who are still a public health problem is iron nutritional anemia. Anemia in young women is still high in Indonesia, it is behind this research. Anemia prevention and prevention efforts are consumption patterns and giving tablets added blood. The general purpose of this research is to know the consumption pattern and consumption habits of TTD with the incidence of anemia in adolescent girls at SMK N I Manggis, Kabupaten Karangasem. This research is an observational research, where the object of research is measured or collected in the same time. This research was conducted at SMKN 1 Manggis, Kabupaten Karangasem. The population of this study were female students at SMKN I Manggis, Kabupaten Karangasem. Sampling technique that is by way of systematic sampling. Data of consumption pattern and consumption habits of TTD in sample was done by interview and Hb level data using measurement tool Hb (Hemoque). The result of spearman rank test showed that there is a significant correlation between consumption pattern seen from food type with anemia incidence with r = 0,798 value with p-value equal to 0.000, there is significant relation between consumption pattern seen from amount of protein consumption with incidence anemia with the value of r = 0.493 with p-value of 0.000, there is a significant relationship between the consumption pattern seen from the consumption of iron with the incidence of anemia with the value of r = 0.594 with p-value of 0.000, there is a significant relationship between consumption patterns seen of vitamin C consumption with anemia incidence with r value = 0,631 with p-value equal to 0.000, there is significant relation between consumption pattern seen from eating frequency with the incidence of anemia with value r = 0,887 with p-value equal to 0.000, there is significant relation between consumption habits tablets added blood with the incidence of anemia d ith value of r = 0.915 with p-value of 0.000.Keywords: Teenage girls, consumption patterns, consumption habits TTD, the incidence of anemia